Report of a novel biological association for Paracrias huberi Gumovsky (Hymenoptera: Eulophidae) with redescription of the female and description of the unknown male - Metz, M. A.; Gates, M. W.; Schauff, M. E. (Zootaxa, 2005)
The female of Paracrias huberi Gumovsky (Hymenoptera: Eulophidae) is redescribed and the previously unknown male described from material collected by George B. Vogt near Plummers Island, Maryland. The species is diagnosed and placed within the current phylogenetic concept for the genus Paracrias. Collection records indicate this species was reared from Homoeolabus analis Illiger (Coleoptera: Attelabidae), which is a leaf-rolling herbivore of Quercus spp. and Castanea spp. (Fagales: Fagaceae), thus expanding the potential host guild range of the genus Paracrias and the known biology of the species. In addition, these records report an association with Q. prinus L., a species native to the eastern United States. The implications of these discoveries in relation to the biology of the plant, host, and wasp parasite are reviewed and discussed.